2014
DOI: 10.1002/cbin.10287
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of ASICs reduces rat hepatic stellate cells activity and liver fibrosis: An in vitro and in vivo study

Abstract: Hepatic fibrosis is a chronic inflammation-associated disease, which is involved in the infiltration of inflammatory cells and releasing of proinflammatory cytokines. In the pathological process, protons are released by damaged cells and acidosis is considered to play a critical role in cell injury. Although the underlying mechanism (s) remain ill-defined, ASICs (acid-sensing ion channels) are assumed to be involved in this process. The diuretic, amiloride, is neuroprotective in models of cerebral ischemia, a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
6
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 21 publications
1
6
1
Order By: Relevance
“…As shown in Figure 1B, the interaction caused ASIC1 expression increase in a time-dependent manner in both Panc-1 cells and PSCs, meaning that the malignant features of tumor were reinforced. It has been reported that an acidic environment can up-regulate ASIC1 expression in liver cancer cells, hepatic stellate cells and PSCs [10,11], but our results indicates that, besides acidity, pancreatic cancer cells and PSCs can promote ASIC1 expression for each other, despite through an uncertain mechanism.…”
Section: Resultscontrasting
confidence: 60%
See 1 more Smart Citation
“…As shown in Figure 1B, the interaction caused ASIC1 expression increase in a time-dependent manner in both Panc-1 cells and PSCs, meaning that the malignant features of tumor were reinforced. It has been reported that an acidic environment can up-regulate ASIC1 expression in liver cancer cells, hepatic stellate cells and PSCs [10,11], but our results indicates that, besides acidity, pancreatic cancer cells and PSCs can promote ASIC1 expression for each other, despite through an uncertain mechanism.…”
Section: Resultscontrasting
confidence: 60%
“…ASIC1 belongs to one of proton-gated ion channels, and is mainly expressed in the mammalian nervous system and several digestive system tumors such as pancreatic cancer, gastric cancer, hepatocellular cancer [7][8][9]. Interestingly, ASIC1 expression also occur in hepatic stellate cells and PSCs, and it mediates acidosis-induced fibrosis, a common non-physiological wound-healing process in liver and pancreatic diseases [10,11]. In particular, ASIC1 regulates the acidity-induced epithelial mesenchymal transition (EMT) of pancreatic cancer cells and activation and autophagy of PSCs, and its expression level is inversely correlated with the tumor prognosis, suggesting its targeting value in pancreatic cancer treatment [8,11].…”
mentioning
confidence: 99%
“…It is expressed in the mammalian nervous system and other tissues, in which it exerts pathophysiological effects [28]. Our previous studies showed that ASIC1a is highly expressed in hepatic fibrosis rat tissues and platelet‐derived growth factor (PDGF)–BB‐induced HSCs, and ASIC1a channels promote liver fibrosis by increasing intracellular Ca 2+ [10,11]. In our study, RT‐PCR and western blotting data also showed that, under acid stimulation, the ASIC1a channel was open, and HSC‐T6 was activated, thus suggesting an increase in the expression of α‐SMA and collagen‐I.…”
Section: Discussionsupporting
confidence: 61%
“…A common feature of these conditions is local tissue acidification and lower pH value [9]. Our previous studies showed that ASIC1a was expressed in rat liver and HSCs, and the level of ASIC1a expression was increased in acid‐activated HSCs, whereas blocking ASIC1a slowed the progression of liver fibrosis [10,11].…”
mentioning
confidence: 99%
“…Through inhibition of ASIC1a channels, PcTx1 was recently showed to inhibit the signs of progression of rat hepatic fibrosis (Wu et al, 2014). In vivo experiments showed that amiloride could significantly alleviate rat liver injury, and reduce pathological tissue damage (Pan et al, 2014).…”
Section: 11-hepatic Fibrosismentioning
confidence: 99%